LITERATURE REVIEW: KEBUTUHAN SPIRITUAL PADA PASIEN DENGAN ULKUS DIABETIK - Subhannur Rahman, Yumi Baida Rahmah (Jurnal Ilmiah Keperawatan, 2020)
Diabetes mellitus is a chronic disease that attacks a part of the body's metabolism that makes a patient a change in behavior. Behavior change along with the treatment process, if the management of the behavior change is good then the healing process also becomes effective. Spiritual needs are ways that can help management change patient behavior. Objective: This study aims to determine the spiritual needs of patients with diabetic ulcers. Method: This study uses a literature study approach used several sources selected based on criteria established by researchers. Results: From 10 journals obtained and conducted a literature review of spiritual needs that were met when the patient met the criteria described in a good relationship to interpersonal, intrapersonal, transpersonal. Conclusion: The problem with poor self-management in people with diabetes mellitus is when a lack of self-motivation makes the healing process ineffective, the spiritual needs that are met the best coping, because the subconscious will create patterns of thought, emotional, and motivation.